Phytol nanoemulsions encapsulated alginate hydrogel beads for the protection and management of alcohol-induced gastric ulcer via nitric oxide synthase and NF-κB/IL-6/TGF-β modulation - Tamer I. M. Ragab; Abdulsalam M. Kassem; Heba M. I. Abdallah; Sally A. El Awdan; Naglaa M. Ammar; Abd El-Nasser G. El Gendy; Basma Emad Aboulhoda; Sherif M. Afifi; Tuba Esatbeyoglu; Enayat A. Omara; Abdelsamed I. Elshamy (PLoS ONE, 2025)
Background Innovative treatment strategies are required for stomach ulcers because of their multifactorial nature. Nanotechnology has emerged as a promising and transformative platform for the formulation and targeted delivery of therapeutic agents. Methods and findings The gastroprotective potential of both in its free form and encapsulated in calcium alginate beads was evaluated against ethanol-induced gastric ulceration in rats. Phytol-loaded nanoemulsions were incorporated into alginate beads to achieve controlled release. Alginate beads showed a pH-dependent release pattern. The release behavior showed a higher release rate at pH 6.8 than at pH 1.2. Phytol release kinetics followed the Korsmeyer–Peppas model, indicating a release mechanism governed by diffusion and polymer relaxation. Rats were pretreated with Phytol and/or nano-Phytol at 10 or 20 mg/kg doses administered one hour before ethanol exposure. Gastric ulcer was induced by administration of EtOH (1 mL/kg, p.o.) 0.5 h after NG-nitro-L-Arginine Methyl Ester (L-NAME) or Aminoguanidine (AMG) injection. Phytol treatment led to a reduction in ulcer index and severity and improved stomach gross morphology. Also, interleukin-6 (IL-6) gastric contents were reduced, whereas transforming growth factor β (TGF-β1) was elevated, and histopathological features were ameliorated. Western blot analysis revealed that nano-Phytol exerted greater inhibitory effects on caspase-3 and Nuclear Factor kappa B (NF-κB) than unformulated Phytol. Interestingly, Phytol’s pharmacological effects on ulcers were enhanced by its nanoformulation in a dose-dependent way without exhibiting any toxicity symptoms. Confocal laser scanning microscopy (CLSM) confirmed significantly improved tissue penetration of nano-Phytol within the stomach layers compared to the Phytol. The Phytol or nano-Phytol gastroprotective effects were modified via the co-administration of L-NAME and AMG. Conclusions The nano-Phytol formulation significantly enhanced the gastroprotective effect of Phytol against ethanol-induced gastric ulcers, primarily through modulation of the nitric oxide (NO) synthase pathway, suppression of inflammation, and upregulation of the growth factor TGF-β1.